Developing algorithms for automatic hypoxing test chasing from the single-channel electrocardiograms: a model experiment - Romanenko, T.M. (PROBLEMS IN PROGRAMMING, 2024)
As an outcome of the COVID-19 pandemic, there is a need to seek new approaches to patients’ rehabilitation, in particular, the novel monitoring technologies enabling the assessment of the functionality and fitness of the cardiovascular and respiratory systems. Hypoxic tests allow for estimating a person’s tolerability to hypoxic conditions and, eventually, for making conclusions about their fitness. Among these tests are the Stange test for which the breath is held after inhaling, and the Genchi test involving holding the breath after exhaling. The important information is the duration of the breath hold. There are methods of direct respiratory signal measurement and indirect ones to control it. They require the use of specialized equipment and specific conditions, often including the need for patient immobilization, therefore, are usually performed in hospitals. Breathing affects the electrocardiogram, which can be used to reconstruct the respiratory signal. Electrocardiogram registration is now a routine procedure performed in hospitals, outpatient clinics, and, due to various options for modern portable single- and multichannel electrocardiographs, even at home by the patients themselves. There are several types of algorithms for obtaining the cardiorespiratory information that rely on different elements of the electrocardiogram signal but they are not suitable for real-time application. This report describes the model experiment developing the optimal algorithm of hypoxic test automatization with the electrocardiogram processing in real-time conditions. We have developed the software called "Harmony" for breathing control during hypoxic test which suggests the starting moment for breath hold. Since the period of breath hold during hypoxic test has specific characteristics on the electrocardiogram that are substantially different from other breathing phases, such as inhaling, exhaling, and calm breathing, the moment of finishing the breath hold can be determined automatically. This allows us to automate hypoxic tests.Prombles in programming 2024; 2-3: 173-179